View PDF HTMLAPIS IN CLOUD DATA SERVICES: A TECHNICAL OVERVIEW - Rohini Isarapu; Sharathchandra Gowda (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive technical article examines the evolution and implementation of Application Programming Interfaces (APIs) in cloud computing environments. It explores the fundamental architecture, integration patterns, security considerations, and performance optimization strategies that shape modern API development. The article analyzes how APIs serve as critical enablers for digital transformation, investigating their role in system integration, data exchange, and enterprise architecture. Through examination of industry research and case studies, it highlights the significance of standardized protocols, microservices adoption, and security frameworks in API implementation. The article also addresses emerging trends, including GraphQL adoption, serverless architectures, and API-first development approaches, while providing insights into best practices for maintaining robust and efficient API ecosystems in cloud environments.